Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Intervening pada Sekretariat Daerah Kabupaten Batanghari - Rizky Laoli; Arna Suryani; Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to describe employee performance, compensation, work environment and work motivation at the Regional Secretariat of Batanghari Regency and to test and analyze the influence of the work environment on employee performance with work motivation as an intervening variable at the Regional Secretariat of Batanghari Regency. This type of research used descriptive verification research. This study uses the PLS analysis method. Based on data processing that compensation is in the proper category. Then to describe the work environment variables, it shows that the work environment for employees at the Regional Secretariat of Batanghari Regency is very good. Furthermore, the description of work motivation variables in the motivated category. While the description of employee performance variables with very high category. Based on the results of the study that compensation has a positive and significant effect on work motivation at the Regional Secretariat of Batanghari Regency. The work environment has a positive and significant effect on work motivation at the Regional Secretariat of Batanghari Regency. Compensation has no significant effect on employee performance at the Regional Secretariat of Batanghari Regency. The work environment has a positive and significant effect on employee performance at the Regional Secretariat of Batanghari Regency and work motivation has a positive and significant effect on employee performance at the Regional Secretariat of Batanghari Regency.